HerMES: Lyman break galaxies individually detected at 0.7 ≤ z ≤ 2.0 in goods-N with Herschel/spire - Burgarella, D.; Heinis, S.; Magdis, G.; Auld, R.; Blain, A.; Bock, J.; Brisbin, D.; Buat, V.; Chanial, P.; Clements, D.; Cooray, A.; Eales, S.; et al. (2011)
As part of the Herschel Multi-tiered Extragalactic Survey we have investigated the rest-frame far-infrared (FIR) properties of a sample of more than 4800 Lyman break galaxies (LBGs) in the Great Observatories Origins Deep Survey North field. Most LBGs are not detected individually, but we do detect a sub-sample of 12 objects at 0.7 < z < 1.6 and one object at z = 2.0. The ones detected by Herschel SPIRE have redder observed NUV – U and U – R colors than the others, while the undetected ones have colors consistent with average LBGs at z > 2.5. The UV-to-FIR spectral energy distributions of the objects detected in the rest-frame FIR are investigated using the code CIGALE to estimate physical parameters. We find that LBGs detected by SPIRE are high-mass, luminous infrared galaxies. It appears that LBGs are located in a triangle-shaped region in the A FUV versus log L FUV = 0 diagram limited by A FUV = 0 at the bottom and by a diagonal following the temporal evolution of the most massive galaxies from the bottom right to the top left of the diagram. This upper envelop can be used as upper limits for the UV dust attenuation as a function of L FUV. The limits of this region are well explained using a closed-box model, where the chemical evolution of galaxies produces metals, which in turn lead to higher dust attenuation when the galaxies age.